2018
DOI: 10.1590/0037-8682-0314-2018
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in the genes encoding toll-like receptors and dectin-1 and susceptibility to invasive aspergillosis: a systematic review

Abstract: Invasive aspergillosis is a common fungal infection in immunocompromised individuals. Some studies have shown that tolllike receptor and dectin-1 genetic polymorphisms may alter signaling pathways, thus increasing an individual's susceptibility to invasive aspergillosis. We investigated the pertinent literature to determine whether polymorphisms in the genes encoding tolllike receptors and dectin-1 increase the susceptibility to invasive aspergillosis. This study systematically reviewed the literature using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
(41 reference statements)
0
10
0
3
Order By: Relevance
“…Reinforcing this notion, it is interesting to notice that human data about dectin-1 genetic polymorphisms and invasive aspergillosis observed this link in immunosuppressed subjects (as cancer or post organ transplantation patients) [12], albeit they lacked a former history of Aspergillus infections previously to their immunodepression. Because clinical immunosuppression (pharmacological or secondary to infections as by HIV) is not lymphocyte-specific, as other immune cells, as NK cells, or even the expression of immune receptors can be affected either [43][44][45][46], it is likely that these depressive states weaken the pulmonary defenses which facilitate the fungus to transpose the lungs.…”
Section: Discussion/conclusionmentioning
confidence: 85%
See 1 more Smart Citation
“…Reinforcing this notion, it is interesting to notice that human data about dectin-1 genetic polymorphisms and invasive aspergillosis observed this link in immunosuppressed subjects (as cancer or post organ transplantation patients) [12], albeit they lacked a former history of Aspergillus infections previously to their immunodepression. Because clinical immunosuppression (pharmacological or secondary to infections as by HIV) is not lymphocyte-specific, as other immune cells, as NK cells, or even the expression of immune receptors can be affected either [43][44][45][46], it is likely that these depressive states weaken the pulmonary defenses which facilitate the fungus to transpose the lungs.…”
Section: Discussion/conclusionmentioning
confidence: 85%
“…However, considering the key role played by dectin-1 in anti-Aspergillus defense suggested by genetic studies that identified Clec7a polymorphisms as risk factors for developing severe aspergillosis [10][11][12], the receptor may also be critical for host defense in extrapulmonary locations. Since A. fumigatus is potentially invasive, able to cause disseminated disease, dectin-1 might also contribute to host defense in the periphery, yet this is still a poorly explored topic and possible effector mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…toll like receptors (TLR) or C-type lectin receptors] alter the signalling pathway of the host's innate immune response, but a wide array of genetic variations in other genes encoding innate immunity components have been documented, along with genetic variation in components of the host's adaptive immunity (e.g. Th-17 or IFN-g, Table 1) (van der Velden et al, 2011;Sainz et al, 2012;Lupiañez et al, 2015;Fisher et al, 2017;Cunha et al, 2018;Cunha and Carvalho, 2019).…”
Section: Understanding Test Utilitymentioning
confidence: 99%
“…A genetic defect in the different types of PRR families makes the host susceptible to fungal infection ( Netea et al, 2012 ). Defect in the CLR Dectin1, encoded by CLEC7A (C-type lectin domain containing 7A) predisposes humans to invasive aspergillosis (IA), chronic mucocutaneous candidiasis (CMC), and recurrent vulvovaginal candidiasis (RVVC) ( Reid et al, 2009 ; Plantinga et al, 2012 ; Cunha et al, 2018 ). The CLEC7A intronic SNPs rs3901533 and rs7309123 are associated with susceptibility to invasive pulmonary aspergillosis (IPA) in patients with hematologic diseases ( Taylor et al, 2007 ; Sainz et al, 2012 ).…”
Section: Genetic Predisposition and Host-pathogen Interactionmentioning
confidence: 99%